Transcriptome profile in the skeletal muscle of progeny from dams protein-supplemented during mid-gestation - Carvalho, Elisa Barbosa de (2021)
Maternal undernutrition and overnutrition during gestation can cause different effects on muscle development and offspring performance. This study aimed to evaluate the differentially expressed genes (DEG), weighed genes co-expression networks (WGCNA), and their biological functions in skeletal muscle of offspring from dams supplemented or not with protein during mid-gestation. From 100 to 200 days of gestation, ten Tabapuã beef cows pregnant of male calves were assigned to one of two treatments: Control [(CON) - supply of basal diet achieving 5.5% of crude protein (CP); n = 6]; or Supplemented [(SUP) - basal diet plus a supplement with 40% of CP provided at the level of 3.5 g/kg of body weight; n = 4]. Muscle samples were collected from the progeny at the beginning of feedlot phase (260d of postnatal age) to RNA-seq, WGCNA and Gene Ontology (GO) enrichment analysis. A total of 310 DEG (q-value < 0.05) were identified for the effect of diet, being 187 and 123 genes down-regulated and up-regulated in the SUP diet, respectively. Within the SUP up-regulated genes, were genes related to insulin receptor signaling pathway (LOC107131843); apoptosis regulation (KRT18, KRT8 and KRT19); negative regulation of lipoprotein lipase activity (ANGPTL4) and potassium ion transmembrane transport (KCNH3). The ENSBTAG00000032057 gene, involved in the ATP synthesis coupled proton transport, were down-regulated in SUP diet. In WGCNA, within hub genes identified in the module negatively associated with diet were ANGPTL4 and ANKRD6 (associated with Wnt signaling pathway); whereas in the modules positively correlated was KLHL10 (homeostasis of number of cells within a tissue). The GO analysis showed that DEG were mainly enriched in potassium ion transmembrane transport, microtubule polymerization or depolymerization and positive regulation of cellular component biogenesis. In conclusion, maternal protein supplementation during mid-gestation modulates the expression of genes involved in important biological process related to myogenesis, lipogenesis, and muscle and adipose tissues metabolism.